Sustained Weight Loss and Risk of Breast Cancer in Women 50 Years and Older: A Pooled Analysis of Prospective Data. (17th December 2019) - Teras, Lauren R; Patel, Alpa V; Wang, Molin; Yaun, Shiaw-Shyuan; Anderson, Kristin; Brathwaite, Roderick; Caan, Bette J; Chen, Yu; Connor, Avonne E; Eliassen, A Heather; Gapstur, Susan M; Gaudet, Mia M; et al.
Abstract: Background: Excess body weight is an established cause of postmenopausal breast cancer, but it is unknown if weight loss reduces risk. Methods: Associations between weight change and risk of breast cancer were examined among women aged 50 years and older in the Pooling Project of Prospective Studies of Diet and Cancer. In 10 cohorts, weight assessed on three surveys was used to examine weight change patterns over approximately 10 years (interval 1 median = 5.2 years; interval 2 median = 4.0 years). Sustained weight loss was defined as no less than 2 kg lost in interval 1 that was not regained in interval 2. Among 180 885 women, 6930 invasive breast cancers were identified during follow-up. Results: Compared with women with stable weight (±2 kg), women with sustained weight loss had a lower risk of breast cancer. This risk reduction was linear and specific to women not using postmenopausal hormones (>2–4.5 kg lost: hazard ratio [HR] = 0.82, 95% confidence interval [CI] = 0.70 to 0.96; >4.5–<9 kg lost: HR = 0.75, 95% CI = 0.63 to 0.90; ≥9 kg lost: HR = 0.68, 95% CI = 0.50 to 0.93). Women who lost at least 9 kg and gained back some (but not all) of it were also at a lower risk of breast cancer. Other patterns of weight loss and gain over the two intervals had a similar risk of breast cancer to women with stable weight. Conclusions: These results suggest that sustained weight loss, even modest amounts, is associated with lower breast cancer risk for women aged 50 years and older. Breast cancer prevention may be a strong weight-loss motivator for the two-thirds of American women who are overweight or obese.